The remineralization potential of cocoa (Theobroma cacao) bean extract to increase the enamel micro hardness - S., Sulistianingsih; I., Irmaleny; Hidayat, Opik Taofik (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2017)
Introduction: Remineralization is the process of returning mineral ions into a hydroxyapatite structure characterized by mineral deposition on the enamel surface. The presence of mineral deposition would affect the microhardness of tooth enamel. Fluorine, as the remineralization agent is known with side effects such as fluorosis. Cocoa bean extract contains theobromine that can be used as an alternative remineralization ingredients. The objectives were to determine enamel microhardness after remineralization using cocoa bean extract as natural material and to compare with fluorine as synthetic material. Methods: Thirty-six maxillary first premolar tooth crowns was cut and planted in the epoxy resin. Teeth were then immersed in demineralization solution at pH 4 for 6 hours. The sample were divided into 2 groups, 18 for the fluorine group and the remaining group of cocoa extract. Vickers microhardness test was used before treatment, both after demineralized and remineralized. Results: The value of enamel microhardness before treatment in the fluorine group was 376.17 VHN as average value and the cocoa extract group was 357.33 VHN. After demineralization in fluorine group was 268.13 VHN and cocoa extract group was 235.93 VHN. After remineralization in fluorine group and cocoa extract group, respectively, 321.08 VHN and 293.86 VHN. The results of the analysis revealed that the level of enamel microhardness after remineralization was not significantly different in both groups (p>0.05). Conclusions: The findings indicated the ability of cocoa extract to increase the microhardness of enamel and implies the potential as a fluorine substitution for remineralization.